The impact of anesthetic techniques on breast cancer recurrence: a systematic review of clinical evidence - Dourado, Aline Tenório; Albuquerque, Amanda Vasconcelos de; Sena, Dayse Figueiredo Ribeiro de; Aguiar, José Lamartine de Andrade (Mastology, 2021)
Introduction: Surgery is the most effective treatment for breast cancer; however, several factors can impair the immune system during the perioperative period, including the anesthetic technique. Since metastasis is the leading cause of death, one of the treatment pillars is to prevent cancer progression. This systematic review will focus on the prospective clinical evidence available on anesthesia’s role in favoring breast cancer recurrence. Methods: The Cochrane Library, Medline, Embase, LILACs, and Web of Science were electronically searched from inception through December 2020 for randomized controlled trials assessing the association of postoperative recurrence and survival with the use of regional anesthesia, opioids, anesthetic adjuncts, and general anesthesia during surgical resection of breast cancer. In total, 711 articles were retrieved. After title and abstract screening and full-text reviews, five randomized controlled trials were selected. Results: Two studies compared inhalation anesthesia with total intravenous anesthesia, while three compared general anesthesia with regional anesthesia and analgesia. There was no significant association between the anesthetic technique and local recurrence, metastasis, or survival. Conclusion: This systematic review did not find an association between the type of anesthesia performed and a higher breast cancer recurrence rate. Up to this time, there is no clinical evidence to support a specific anesthetic technique for malignant breast tumor resection surgeries.